2017
DOI: 10.1039/c7ob01457k
|View full text |Cite
|
Sign up to set email alerts
|

The preference for dual-gold(i) catalysis in the hydro(alkoxylation vs. phenoxylation) of alkynes

Abstract: This version is available at https://strathprints.strath.ac.uk/61289/ Strathprints is designed to allow users to access the research output of the University of Strathclyde. Unless otherwise explicitly stated on the manuscript, Copyright © and Moral Rights for the papers on this site are retained by the individual authors and/or other copyright owners. Please check the manuscript for details of any other licences that may have been applied. You may not engage in further distribution of the material for any pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 97 publications
0
18
0
Order By: Relevance
“…[69,70,[79][80][81][82][71][72][73][74][75][76][77][78] In the majority of homogeneous Au catalysts, Au exists in the + 1 oxidation state. [103][104][105][106][107] In the past, the applications of Au I in enantioselectiver eactions have been considered challenging. The relativistic effects cause the contraction of 6s and 6p orbitals andt he expansion of 5d orbitals in Au I .…”
Section: Introductionmentioning
confidence: 99%
“…[69,70,[79][80][81][82][71][72][73][74][75][76][77][78] In the majority of homogeneous Au catalysts, Au exists in the + 1 oxidation state. [103][104][105][106][107] In the past, the applications of Au I in enantioselectiver eactions have been considered challenging. The relativistic effects cause the contraction of 6s and 6p orbitals andt he expansion of 5d orbitals in Au I .…”
Section: Introductionmentioning
confidence: 99%
“…In this frame, a case that partially deviates from this general trend, is represented by the hydrophenoxylation of diphenylacetylene catalyzed by the dinuclear gold(I) complex [{Au(IPr)} 2 (µ-OH)][BF 4 ], studied in detail by Nolan and coworkers [14][15][16]. In this reaction, the gold catalyst is not only involved in the alkyne activation by forming the A-type π-complex (Scheme 1), but also reacts at the first stage of the reaction with phenol, forming the species [{Au(IPr)} 2 (µ-OPh)] + , thus also activating the nucleophile [15].…”
Section: Introductionmentioning
confidence: 99%
“…For the sake of consistency, single point energy calculations on the Gaussian09 optimised structures have been undertaken for the ADF calculations. Part of the geometry optimisations is extracted from past work of Poater and co‐workers , …”
Section: Computational Detailsmentioning
confidence: 99%
“…Note that [Au] = Au(IMe). [23] Heterobimetallic complexes have been also matter of study due to the fact that the bifunctionality of different metals can lead to unique reactivity. Recent work by Cazin et al reported the hydrophenoxylation of internal alkynes with heterobimetallic Cu-NHC/Au-NHC systems, [35] in line with previous works on two metal moieties bearing different metal nature.…”
Section: Introductionmentioning
confidence: 99%